Razvoj prebivalstva v ljubljanski urbani regiji - Rebernik, Dejan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2004)
The paper presents the main characteristic of population development and urbanisation processes in Ljubljana and Ljubljana urban region. Up to the end of the seventies fast population growth was a consequence of strong immigration from rural parts of Slovenia and the rest of Yugoslavia. In the eighties and nineties deconcentration of population within the region with intense suburbanisation and depopulation of inner city and older residential neighbourhoods were the main urbanisation processes. In the second half of the nineties the highest population growth was recorded in dispersed rural settlements in the periphery of the region. In some parts of the inner city reurbanisation and gentrification occurred.
Keywords: urbana geografija; mesta; prebivalstvo; demogeografija; gibanje prebivalstva; urbanizacija; Ljubljana